# I Sum of the first n squares?

Tags:
1. Jan 18, 2017

### sleepwalker27

I found a deduction to determinate de sum of the first n squares. However there is a part on it that i didn't understood.

We use the next definition: $$(k+1)^3 - k^3 = 3k^2 + 3k +1$$, then we define $$k= 1, ... , n$$ and then we sum...

$$(n+1)^3 -1 = 3\sum_{k=0}^{n}k^{2} +3\sum_{k=0}^{n}k+ n$$

The left side of the equality is the one that i didn't understood. Why $$(k+1)^3 - k^3$$ changes in that way?

2. Jan 18, 2017

### haruspex

((n+1)3-n3) + (n3-(n-1)3) + ((n-1)3-(n-2)3) ....

3. Jan 18, 2017

### Orodruin

Staff Emeritus
The first term for k is cancelled by the second term for k+1. This leaves the first term for k=n and the second for k=1.

4. Jan 19, 2017

### Stephen Tashi

A general definition is $\triangle F(k) = F(k+1) - F(k)$
So $\triangle ( k^3) = (k+1)^3 - k^3$

A general trick is the "telescoping sum":
$\sum_{k=1}^n \triangle F(k) = (F(1+1) - F(1)) + ( F(2+1) - F(2)) + (F(3+1) - F(3)) + ...+ F(n+1) - F(n)$
$= ( F(2) - F(1)) + (F(3) - F(2)) + (F(4) - F(3)) + ... + (F(n+1) - F(n))$
$= -F(1) + (F(2) - F(2)) + (F(3) - F(3)) + ...+ (F(n) - F(n))+ F(n+1)$
$= F(n+1) - F(1)$

So $\sum_{k=1}^n \triangle k^3 = (n+1)^3 - 1^3$

5. Jan 19, 2017

### mathman

$(k+1)^3=k^3+3k^2+3k+1$. Expand the expression.